USING THE MODEL OF BLENDED LEARNING IN TEACHING THE ENGLISH LANGUAGE TO STUDENTS OF NON-LANGUAGE SPECIALTIES - Remizantseva , K. (Problems of Engineer-Pedagogical Education, 2019)
The scientific-theoretical analysis of the "blended learning" concept as an innovative model of teaching foreign languages in general and the problem of using blended learning technology in teaching English in particular at higher education institutions are proved in the paper. The article provides a comparative analysis of the foreign and domestic researchers’ perspectives in defining the term "blended learning" as a modern universal learning tool that combines traditional and e-learning technologies and corresponds to students’ individual requirements. The authors have determined that "blended learning" is a holistic learning process, which implies that one part of cognitive activity is conducted in the classroom under the direct guidance of a teacher, and another part of students’ activity is taken in a distance form, with the predominance of independent types of work. The advantages and disadvantages of the blended learning model in the English language teaching process are analysed, its effectiveness in modern education is substantiated. The possibilities of increasing the efficiency of the educational process through the introduction of modern information and communication technologies in the context of engineering and pedagogical universities are considered here. The ways of building students’ competences which are necessary for studying by blended learning technologies are defined. Attempts to introduce some of the blended learning integrative components that should be taken into account when developing, implementing, and evaluating this technology are made in the article. The basic structural approaches to the introduction of blended learning technology at the non-linguistic higher education institution during English classes are offered. The features of using the Moodle e-learning platform are considered in the article, the factors that are important for organizing the distance learning process of learning foreign languages are given here too. The author researches the personal experience of using the Moodle e-learning platform during English language classes at the Engineering Pedagogics Academy on the example of the "Foreign Language of Professional and Business Communication" course for 4th year students of bachelor level degree. Keywords: blended learning, students, the English language, higher education institutions,